2017
DOI: 10.1038/srep42609
|View full text |Cite
|
Sign up to set email alerts
|

Loss of OxyR reduces efficacy of oxygen respiration in Shewanella oneidensis

Abstract: In many bacteria, OxyR is the major regulator controlling cellular response to H2O2. A common phenotype resulting from OxyR loss is reduced growth rate, but the underlying mechanism is unknown. We demonstrated in Shewanella oneidensis, an important research model for applied and environmental microbes, that the defect is primarily due to an electron shortage to major terminal oxidase cytochrome cbb3. The loss of OxyR leads to enhanced production of electron carriers that compete for electrons against cytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…However, another possible explanation of these data is that OxyR plays a role in fundamental cellular metabolism. Loss of oxyR reduces the efficacy of oxygen respira- tion in Shewanella oneidensis and increases the transcription of cytochrome bd (39); while no significant differences in cyd operon expression were noted in the RNA sequencing of the A. baumannii ΔoxyR strain in LB, it is possible that other aspects of central metabolism are altered in this strain. Much remains to be learned about the function of OxyR in pathogenic organisms, including its potential role in central metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…However, another possible explanation of these data is that OxyR plays a role in fundamental cellular metabolism. Loss of oxyR reduces the efficacy of oxygen respira- tion in Shewanella oneidensis and increases the transcription of cytochrome bd (39); while no significant differences in cyd operon expression were noted in the RNA sequencing of the A. baumannii ΔoxyR strain in LB, it is possible that other aspects of central metabolism are altered in this strain. Much remains to be learned about the function of OxyR in pathogenic organisms, including its potential role in central metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…When iron concentrations fell below a minimum threshold, the biosynthesis of cyt c is abolished, leading to an inability to carry out the respiration of nonoxygen EAs. However, heme b remains to be synthesized, albeit at reduced levels, allowing aerobic growth by cyt bd oxidase, an enzyme that is inferior to cyt cbb 3 oxidase in efficiency but that plays an important role in combating various stresses (57,64,65). Clearly, the total iron levels in the fur mutant, although substantially decreased, are above the threshold, because cyt c is synthesized to some extent, and the respiration of nonoxygen EAs occurs.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that OxyR in excess negatively influences growth but not viability. We have previously shown that growth defect of the oxyR mutant is largely attributable to reduced efficacy of oxygen respiration, indirect effects of the oxyR mutation (20). We speculate the same mechanism accountable for the growth inhibition of excessive OxyR; efforts to test this notion are underway.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the S. oneidensis OxyR resembles those of Neisseria, working as both a repressor and an activator. Nevertheless, it carries novel features that have never been observed from OxyRs studied to date, including compromised resistance to exogenous H 2 O 2 , intertwined regulation with OhrR, and non-exchangeable functionality with E. coli OxyR (18)(19)(20)23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation